PENGARUH PERMAINAN BINGO TERHADAP PENGENALAN KOSAKATA BAHASA INGGRIS PADA ANAK DI TAMAN KANAK-KANAK KARTIKA 1-7 PADANG - Ririn Marvelia Putri; Elise Muryanti; Rismareni Pransiska; Tisna Syafnita (STKIP Subang, 2025)
From initial observations conducted by researchers on English vocabulary recognition skills at Kartika 1-7 Padang Kindergarten, it appears that children's English vocabulary recognition skills are still low because teachers only teach through flashcards. Therefore, educators need a variety of activities to improve children's English vocabulary recognition skills. One such activity is playing Bingo. This study aims to examine the effect of Bingo on children's English vocabulary recognition skills at Kartika 1-7 Padang Kindergarten. This study uses a quantitative method with a quasi-experimental design in the experimental and control classes. The population of this study is all children at Kartika 1-7 Padang Kindergarten in the 2025/2026 academic year. The sample was taken using purposive sampling, with class B5 as the experimental class consisting of 11 children and class B6 as the control class consisting of 11 children. The data collection technique used a test consisting of 5 statement items, and the data analysis technique used in this study was to compare the difference between the two mean values, so a T-test was performed. The data was processed using the SPSS Ver 26 For Windows application. Based on the post-test hypothesis test, the sig value (2-tailed) was 0.000 < 0.05. Thus, there is a significant difference between the bingo game and the treatment given by the teacher on the ability to recognize English vocabulary in children. It can be concluded that the Bingo game has an effect on the ability to recognize English vocabulary in children aged 5-6 years.